Keywords: Antioxidant, DPPH, Turmeric Instant Powder, UV-Vis Spectrophotometer and IC50 value. - muhammad alfian (Fakultas Farmasi Institut Kesehatan DELI HUSADA Deli Tua, 2023)
Abstract Turmeric and tamarind herbal medicine is one of the drinks with turmeric and tamarind as raw materials which is quite widely consumed by the community, either in liquid form or in powder form. Jamu turmeric acid can be used to prevent the negative effects of free radicals on the body because there are active antioxidant compounds, besides that it can be used as a natural antioxidant. There are many natural antioxidants in nature, one of which is in traditional medicine. The content of Jamu turmeric acid is curcuminoids where this compound is useful as an anti-inflammatory and antioxidant. This study aims to determine the antioxidant activity of instant turmeric powder drink produced by of UMKM Healthy Partners, Kiringan Bantul herbal tourism village, using the DPPH method (2,2-diphenyl-1-picrylhydrazyl). The absorbance measurement to determine the antioxidant activity of each sample of turmeric tamarind powder was tested using a UV-Vis spectrophotometer at a maximum wavelength of 516 nm. Determination of antioxidant activity by the DPPH method is expressed by the IC50 (Inhibiton Concentration 50) value. The results showed that the antioxidant activity of the instant turmeric powder drink (Curcuma domestica val.-tamarindus indica l.) produced by Mitra Sehat SME in the Jamu Kiringan Tourism Village, Bantul, was included in the very weak category with an IC50 value of each sample successively. The participants were sample A of (276.005 ppm), sample B of (265.434 ppm), and sample C of (256.183 ppm). Keywords: Antioxidant, DPPH, Turmeric Instant Powder, UV-Vis Spectrophotometer and IC50 value.